Selective Complexometric Determination of Palladium by Using L-Cystine as Releasing Agent - Chandrashekhara, K.G.; Gopalakrishna Bhat, N.; Nagaraj, P. (Asian Journal of Chemistry, 2015)
A complexometric method for the determination of palladium in the presence of other metal ions based on the selective masking ability of L-Cystine towards palladium is described. Palladium(II) is complexed with excess of EDTA and the surplus EDTA is back titrated with standard lead nitrate solution at 5 to 6 pH by using hexamine and xylenol orange as an indicator. L-Cystine (0.02 M) solution is then added to release EDTA quantitatively from Pd-EDTA complex. The EDTA released is back titrated with standard lead nitrate solution as before. The method works well in the concentration range 2 to 34 mg of Pd with relative error £ 0.94 % and relative standard deviation £ 1.21 %. The method has been successfully applied to the determination of Pd in alloy composition and complexes.